RAJADESA: MODEL PEMBELAJARAN P5 BERBASIS NILAI PANCASILA PADA TRADISI BERSIH DESA ARJOWILANGUN - Hamidah, Latifah Winda; Sukmawan, Sony; Warsiman (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
Globalization has influenced cultural values and national identity, leading to the emergence of individualism and cultural intervention. Bersih Desa tradition of Arjowilangun, which embodies Pancasila values, is highly relevant as a means of character education for the younger generation. This study aims to explore the Pancasila values in the Bersih Desa tradition and develop an experiential learning-based model for the Pancasila Student Profile Strengthening Project (P5). This research employs a qualitative approach with a field research design. The findings reveal that Pancasila values, such as divinity, humanity, justice, unity, and democracy, are present in every stage of the Bersih Desa tradition. Additionally, teaching Pancasila values through the RAJADESA field trip model effectively integrates Pancasila with character education. This learning model strengthens students' understanding of national identity, fosters social interaction, and promotes local culture sustainably.